Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Sekwan Kota “P” - Rofidah, Siti; Fakhri, Rizqi (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This research aims to examine the influence of the Work Environment on the performance of Sekwan Kota “P” Office Employees. The research sample consisted of 41 people because the researcher was not included in the sample. The research results show that the Work Environment has a positive and significant influence on the performance of Sekwan Kota “P” Office Employees. The validity test shows that all statement items are valid with a value of rcount > rtable (0.3081). The results of simple regression produce the equation Y = 12.524+ 0.410X. The t test shows that the tcount (2.487) is greater than ttable (2.02269) with a significance level of 0.017 < 0.05. The coefficient of determination R2 of 0.137 indicates that the contribution of the Work Environment variable to employee performance is 13.7% while 86.3% is influenced by other factors not examined in this research.